2020
DOI: 10.1007/s12035-020-01905-6
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexia Candidate Gene and Ciliary Gene Expression Dynamics During Human Neuronal Differentiation

Abstract: Developmental dyslexia (DD) is a neurodevelopmental condition with complex genetic mechanisms. A number of candidate genes have been identified, some of which are linked to neuronal development and migration and to ciliary functions. However, expression and regulation of these genes in human brain development and neuronal differentiation remain uncharted. Here, we used human long-term self-renewing neuroepithelial stem (lt-NES, here termed NES) cells derived from human induced pluripotent stem cells to study n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Ciliogenesis was thus found as a prominent aspect during LUHMES neuronal differentiation. Similar ‘ciliary’ observations were made for the differentiation from human neuroepithelial stem (NES) cells and induced pluripotent stem cells (iPSCs) into neurons (Bieder et al, 2020 in press).…”
Section: Resultsmentioning
confidence: 56%
“…Ciliogenesis was thus found as a prominent aspect during LUHMES neuronal differentiation. Similar ‘ciliary’ observations were made for the differentiation from human neuroepithelial stem (NES) cells and induced pluripotent stem cells (iPSCs) into neurons (Bieder et al, 2020 in press).…”
Section: Resultsmentioning
confidence: 56%
“…The complex DYX1C1/CPAP/DCDC2 might act in conjunction in migrating neurons, possibly independently of cilium and centrosome. Interestingly, DYX1C1 is highly upregulated in differentiating human neurons (32). Further studies in human stem cell derived neurons might shed more light on the role of these genes in neuronal migration.…”
Section: Discussionmentioning
confidence: 95%
“…DYX1C1 has been proposed as a cytoplasmic axonemal dynein assembly factor (16, [27][28][29][30]. Recent studies have strengthened a role of DCDC2 and DYX1C1 also in primary cilia and human neurons (31,32).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing awareness that domain general genes have an important role to play in the genetics of reading 77, 78 . Additionally, four out of five of these genes play a role in the neuron migration pathway, which is often hypothesized to be causal to reading disabilities 79, 80 . These findings build on prior work which showed that neuron migration was overrepresented in genetic findings for typical and atypical readers 19, 81 .…”
Section: Discussionmentioning
confidence: 99%